Principles of public international law: a modern approach - Eishan Jan, Mohammad Naqib (IIUM Press, 2009)
Principles of public international law: a modern approach addresses a spectrum of legal issues that affect the day to day affairs of the international community. Based on original sources, it analyzes and applies, with accuracy and elasticity, potentially basic principles of public international law to the issues so as to provide a better and easier understanding of the law. It provides a framework that helps both students and practitioners of the law in theor careers.